Origin and transportation history of lunar breccia 14311. (17th February 2017) - Merle, Renaud E.; Nemchin, Alexander A.; Whitehouse, Martin J.; Pidgeon, Robert T.; Grange, Marion L.; Snape, Joshua F.; Thiessen, Fiona
Abstract: In this paper, we compare the U‐Pb zircon age distribution pattern of sample 14311 from the Apollo 14 landing site with those from other breccias collected at the same landing site. Zircons in breccia 14311 show major age peaks at 4340 and 4240 Ma and small peaks at 4110, 4030, and 3960 Ma. The zircon age patterns of breccia 14311 and other Apollo 14 breccias are statistically different suggesting a separate provenance and transportation history for these breccias. This interpretation is supported by different U‐Pb Ca‐phosphate and exposure ages for breccia 14311 (Ca‐phosphate age: 3938 ± 4 Ma, exposure age: ~550–660 Ma) from the other Apollo 14 breccias (Ca‐phosphate age: 3927 ± 2 Ma, compatible with the Imbrium impact, exposure age: ~25–30 Ma). Based on these observations, we consider two hypotheses for the origin and transportation history of sample 14311. (1) Breccia 14311 was formed in the Procellarum KREEP terrane by a 3938 Ma‐old impact and deposited near the future site of the Imbrium basin. The breccia was integrated into the Fra Mauro Formation during the deposition of the Imbrium impact ejecta at 3927 Ma. The zircons were annealed by mare basalt flooding at 3400 Ma at Apollo 14 landing site. Eventually, at approximately 660 Ma, a small and local impact event excavated this sample and it has been at the surface of the Moon since this time. (2) Breccia 14311 was formed by a 3938 Ma‐old impact. The location of the sample is not known at that time but at 3400 Ma, it was located nearby or buried by hot basaltic flows. It was transported from where it was deposited to the Apollo 14 landing site by an impact at approximately 660 Ma, possibly related to the formation of the Copernicus crater and has remained at the surface of the Moon since this event. This latter hypothesis is the simplest scenario for the formation and transportation history of the 14311 breccia.